2017
DOI: 10.1002/ajpa.23160
|View full text |Cite
|
Sign up to set email alerts
|

Hadza sleep biology: Evidence for flexible sleep‐wake patterns in hunter‐gatherers

Abstract: This study showed that circadian rhythms in small-scale foraging populations are more entrained to their ecological environments than Western populations. Additionally, Hadza sleep is characterized as flexible, with a consistent early morning sleep period yet reliance upon opportunistic daytime napping. We propose that plasticity in sleep-wake patterns has been a target of natural selection in human evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…For TST, we used a value of 7 hr, based on a variety of sources from Western and non‐Western populations, as follows. In non‐Western populations, our previous research on both Malagasy agriculturalists and Hadza foragers suggests that 7 hr is conservative, with these studies estimating human sleep at 6.5 and 6.25 hr, respectively (Samson, Crittenden, Mabulla, Mabulla, & Nunn, ; Samson, Manus, Krystal, Fakir, Yu, & Nunn, ). This also corresponds to findings from a recent study of three subsistence societies without electricity that also included the Hadza (Yetish et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For TST, we used a value of 7 hr, based on a variety of sources from Western and non‐Western populations, as follows. In non‐Western populations, our previous research on both Malagasy agriculturalists and Hadza foragers suggests that 7 hr is conservative, with these studies estimating human sleep at 6.5 and 6.25 hr, respectively (Samson, Crittenden, Mabulla, Mabulla, & Nunn, ; Samson, Manus, Krystal, Fakir, Yu, & Nunn, ). This also corresponds to findings from a recent study of three subsistence societies without electricity that also included the Hadza (Yetish et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a laboratory study found that people adopted biphasic sleep when exposed to 14 hr of darkness each night (Wehr, 1992). There is also evidence of biphasic sleep in some contemporary communities without electricity (Samson et al, 2017b), but not others (Beale et al, 2017;de la Iglesia et al, 2015;Peixoto, da Silva, Carskadon, & Louzada, 2009;Samson, Crittenden, Mabulla, Mabulla, & Nunn, 2017a;Yetish et al, 2015). Despite some dispute about the likely origins of biphasic sleep in humans (Ekirch, 2016;Yetish et al, 2015), sleep in western societies has clearly changed in recent history (Ekirch, 2015).…”
Section: Human Sleep: Real-world Comparisonsmentioning
confidence: 99%
“…The implication is that sleep duration from non‐industrial, non‐electric populations would represent a healthier, species‐typical sleep pattern. Yet recent sleep research conducted among Hadza and San hunter‐gatherers and Tsimane horticulturalists cast doubt on this supposition, finding that their average nightly sleep duration is largely comparable to that of people living in the United States, despite lacking electricity and maintaining a subsistence lifestyle (Samson, Crittenden, Mabulla, Mabulla, & Nunn, ; Yetish et al, ). Building on these findings, this study addresses another common supposition in sleep research: that “normal” sleep duration is generally consistent from night‐to‐night for a given individual (Gaines et al, ; Sharpley, Solomon, & Cowen, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%